Pengaruh Responsiveness Perawat dalam Praktik Komunikasi Terapeutik terhadap Kepuasan Pasien Instalasi Rawat Inap RSU Haji Surabaya - Ajenk Nanda Saprilla (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: Patient’s satisfaction is one of indicators measured in the hospital minimum service standards. In Installation of Inpatient (IRNA) of Haji Surabaya hospital, there are 17 indicators, but only nine are met (52.94%). One of them is patients’ satisfaction level amounted to 74.35% out of the standard (82%). The high number of complaints on nurses’ competence in providing services causes the unachieved patients’ satisfaction. There were 61 complaints from 2014 to 2017.Aim: This study aimed to analyze the influence of nurses’ responsiveness to patients’ satisfaction of in-patient installation (IRNA) at Haji Surabaya Hospital.Method: The questionnaires used Likert scale 1-5 for independent variables and dependent variables. The scoring scales for the independent variable or nurses’ responsiveness range from strongly disagree to strongly agree. Meanwhile, the scoring scale for the dependent variable ranges from very dissatisfied to very satisfied.Results: The findings indicated that there was a significant influence of responsiveness on patients’ satisfaction amounted to 0.003 (<α = 0.05). This indicated that the better assessment on the nurses’ responsiveness is, themore satisfied the patients are at in-patient installation (IRNA), Haji Surabaya Hospital.Conclusion: It can be concluded that more than 20% of responses was satisfied with the nurses’ responsiveness. The hospital needs to hold a human resource training especially a nurse-patient therapeutic communication training for maintaining the service quality at the hospital.Keywords: hospitalization, patient, responsiveness, satisfaction